Bykova, M. F.; Forster, M. N. & Steiner, L. (eds.) The Palgrave Handbook of Russian Thought [O manual Palgrave do pensamento russo]. Springer Verlag, 2021. XXVII, 814 р. - Osovsky , Oleg; Dubrovskaya, Svetlana; Chernetsova, Ekaterina (Bakhtiniana. Revista de Estudos do Discurso, 2022)
Resenha